The visibility of women writers from nineteenth-century in the public sphere of the press. - Lledó Patiño, Mercedes (Estudios sobre el Mensaje Periodístico, 2012)
The professional relationships of nineteenth-century journalists with women writers of the intelectual circle of Madrid during this century, together with their renown in the Spanish press, ratify one of the first pages in the book of gender equality. From the decade of 1840, Spanish journalism gave visibility to texts signed by women, and many newspapers and magazines started to spread women’s talent and thought, which had been rejected until that moment. A group of friendships and geographic links gave rise to these first collaborations. The names of Gertrudis Gómez de Avellaneda, Carolina Coronado, Robustiana Armiño de Cuesta, Amalia Fenollosa and Dolores Cabrera y Heredia appeared together in the literary magazine Los hijos de Eva (Eva’s Children), founded and directed by Ventura Ruiz Aguilera, a writer and a journalist from Salamanca.